Beyond Type 1 Regulatory T Cells: Co-expression of LAG3 and CD49b in IL-10-Producing T Cell Lineages - Huang, Weishan; Solouki, Sabrina; Carter, Chavez; Zheng, Song-Guo; August, Avery (Frontiers in Immunology, 2018)
Type 1 regulatory CD4+ T (Tr1) cells express high levels of the immunosuppressive cytokine IL-10 but not the master transcription factor Foxp3, and can suppress inflammation and promote immune tolerance. In order to identify and obtain viable Tr1 cells for research and clinical applications, co-expression of CD49b and LAG3 has been proposed as a unique surface signature for both human and mouse Tr1 cells. However, recent studies have revealed that this pattern of co-expression is dependent on the stimulating conditions and the differentiation stage of the CD4+ T cells. Here, using an IL-10GFP/Foxp3RFP dual reporter transgenic murine model, we demonstrate that co-expression of CD49b and LAG3 is not restricted to the Foxp3- Tr1 cells, but is also observed in Foxp3+ T regulatory (Treg) cells and CD8+ T cells that produce IL-10. Our data indicate that IL-10-producing Tr1 cells, Treg cells and CD8+ T cells are all capable of co-expressing LAG3 and CD49b in vitro following differentiation under IL-10-inducing conditions, and in vivo following pathogenic insult or infection in the pulmonary mucosa. Our findings urge caution in the use of LAG3/CD49b co-expression as sole markers to identify Tr1 cells, since it may mark IL-10-producing T cell lineages more broadly, including the Foxp3- Tr1 cells, Foxp3+ Treg cells and CD8+ T cells.